Konsep Ta’aruf Surah dalam Surah Al-Hujurat Ayat 13: Studi Komparatif Tafsir Ibnu Katsir, Ar-Razi, As-Sa'di, dan Al-Munir - Nurlela N; Nurul Istianah; Panca Sakti Kamal; Zakiyuddin Rahim; Muhammad Yusuf; Abdul Rahman Sakka (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Ta'aruf is one of the key Qur'anic concepts governing patterns of socio-religious interaction amid the diversity of tribes, nations, and cultures. The phenomenon of social disintegration frequently triggered by identity-based sentiments makes a comprehensive understanding of this concept increasingly urgent to examine. This study aims to explore and compare the interpretations of four exegetes from different eras and methodological backgrounds—Ibn Kathir, Ar-Razi, As-Sa'di, and Wahbah az-Zuhaili in Tafsir Al-Munir—regarding the concept of ta'aruf in Surah Al-Hujurat, verse 13. This research employs a descriptive-analytical qualitative method with a library research approach and a comparative exegesis (tafsir muqaran) framework. Primary data are drawn from the exegetical works of the four scholars, while secondary data are obtained from relevant books, journals, and scholarly articles. At this stage of the study, the analysis focuses on Ibn Kathir's interpretation as the point of departure, which demonstrates that the diversity of tribes and nations was created by Allah not as a basis for mutual pride, but as a means of mutual acquaintance (ta'aruf), with piety (taqwa) as the sole legitimate measure of nobility in His sight. The comparative analysis with the interpretations of Ar-Razi, As-Sa'di, and Al-Munir, along with the formulation of common ground among the four, will be completed in a subsequent stage of research. This study is expected to contribute to strengthening the discourse on religious moderation and identity-based conflict resolution within multicultural societies.